Association and risk of hypercholesterolemia among patients with prediabetes from a medical center in Villa El Salvador, Lima, Peru - Guevara Tirado, Alberto (2024)
Objective: To evaluate the association and risk of hypercholesterolemia among adult patients with prediabetes treated at a medical center in the district of Villa El Salvador in Lima, Peru. Materials and methods: An analytical, prospective and cross-sectional study conducted with data from medical consultation records of 749 patients treated at a polyclinic in the district of Villa El Salvador in Lima, Peru. Asymptomatic adult patients who had routine and preventive checkups were included in the research. Patients with endocrine and metabolic disorders or being treated with hypoglycemic drugs were excluded. The study variables were sex, hypercholesterolemia and prediabetes. The association analysis was performed using the chi-square test and the risk was evaluated by means of the odds ratio. In addition, the multivariate analysis was conducted through a binary logistic regression, and an alpha value of 0.05 and a confidence level of 95 % were considered as the cut-off point to determine the statistical significance. Results: There was a statistically significant association between prediabetes and hypercholesterolemia. Females with prediabetes were 1.66 times more likely to develop hypercholesterolemia than females with normal baseline glucose levels, while males with prediabetes were 2.37 times more likely to have high cholesterol than males with normal baseline blood glucose levels. Conclusions: Prediabetes is associated with hypercholesterolemia, thus increasing its risk. It is justifiable to carry out the joint measurement of fasting total cholesterol and baseline glucose in disease prevention and health promotion campaigns, regular checkups and follow-up of patients with risk factors for diabetes, prediabetes and hypercholesterolemia. This helps reduce the hemodynamic and cardiovascular consequences of high cholesterol levels and the worsening of the joint morbidity and mortality of chronic hyperglycemia.